EMISI KARBON, NILAI PERUSAHAAN, DAN PENGUNGKAPAN LAPORAN KEUANGAN: TINJAUAN TEORI LEGITIMASI DAN TEORI SINYAL (Perusahaan Energi Batubara yang Terdaftar di BEI Tahun 2022-2023) - Rizqy Kurnia Mulyadi; Endang Kiswara (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the relationship between three main aspects: total carbon emissions, voluntary carbon emissions disclosure, and firm value among coal companies listed on the Indonesia Stock Exchange for the period 2022-2023.  Using legitimacy and signalling theory approaches, this study seeks to understand the motivation of companies in disclosing carbon emissions and its impact on market value. This research uses a comparative qualitative descriptive method with descriptive statistics. The results of the study show that overall, PT Bayan Resources Tbk. stands out as the company with the best environmental performance, while PT TBS Energi Utama Tbk. consistently records the worst performance in various carbon emission ratios. PT Harum Energy Tbk. did excel in the aspect of voluntary disclosure, but due to the high ratio of carbon emission to operating income which reached 133, its final environmental performance score became less optimal than PT Bayan Resources Tbk